GLOBAL SEISMICITY OF 1982 - CENTROID-MOMENT TENSOR SOLUTIONS FOR 308 EARTHQUAKES - Dziewonski, A; Friedman, A; Giardini, D; Woodhouse, J (1983)
The centroid-moment tensor analysis is applied to digital recordings of 308 moderate and large earthquakes that occurred during 1982 and were recorded by the Global Digital Seismograph Network (GDSN) and International Deployment of Accelerometers (IDA) networks. The tables contain numerical results for all events. A graphical representation of the source geometry is shown for the full moment tensor solution, as well as for the "best double couple". © 1983.